2017
DOI: 10.3390/app7080834
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Removal of Bisphenol-A and Nonylphenols from Pretreated Domestic Wastewater by Tropical Horizontal Sub-SurfaceConstructed Wetlands

Abstract: Bisphenol A (BPA) and nonylphenols (NPs), with a high potential to cause endocrine disruption, have been identified at levels of nanograms per liter and even micrograms per liter in effluents from wastewater treatment plants. Constructed wetlands (CWs) are a cost-effective wastewater treatment alternative due to the low operational cost, reduced energy consumption, and lower sludge production, and have shown promising performance for treating these compounds. A CW pilot study was undertaken todetermine its pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, the relatively slow sorption behaviour for this compound was unexpected given its relatively hydrophobic character (log K ow ∼ 3.80–4.77). 39 Though others have observed a correlation, log K ow has not always been observed to be a good predictor of sorption affinity. 40 This suggests that there are other factors at the microplastic–contaminant interface that may influence sorption kinetics.…”
Section: Resultsmentioning
confidence: 97%
“…However, the relatively slow sorption behaviour for this compound was unexpected given its relatively hydrophobic character (log K ow ∼ 3.80–4.77). 39 Though others have observed a correlation, log K ow has not always been observed to be a good predictor of sorption affinity. 40 This suggests that there are other factors at the microplastic–contaminant interface that may influence sorption kinetics.…”
Section: Resultsmentioning
confidence: 97%
“…Constructed wetlands are a cost-effective wastewater treatment alternative due to their low operational cost, reduced energy consumption, and low sludge production [18]. Toro-Vélez et al [19], in their study "Longitudinal Removal of Bisphenol-A and Nonylphenols from Pretreated Domestic Wastewater by Tropical Horizontal Sub-Surface Constructed Wetlands", assessed the removal of two endocrine disrupting TrOCs, namely, Bisphenol A and nonylphenols, by an alternative wastewater treatment option: a constructed wetland. Toro-Vélez et al [19] confirmed the significant removal of the target pollutants from wastewater by this process.…”
Section: Removal Of Trace Organic Contaminantsmentioning
confidence: 99%
“…Toro-Vélez et al [19], in their study "Longitudinal Removal of Bisphenol-A and Nonylphenols from Pretreated Domestic Wastewater by Tropical Horizontal Sub-Surface Constructed Wetlands", assessed the removal of two endocrine disrupting TrOCs, namely, Bisphenol A and nonylphenols, by an alternative wastewater treatment option: a constructed wetland. Toro-Vélez et al [19] confirmed the significant removal of the target pollutants from wastewater by this process. Through a pilot study, they demonstrated that a native plant from the tropics could contribute to the enhanced removal of TrOCs by constructed wetlands.…”
Section: Removal Of Trace Organic Contaminantsmentioning
confidence: 99%